Formation in the Highlands of Eastern Turkey: An Overview From the Bronze to Iron Ages - Aylin Ü. Erdem (Anadolu Araştırmaları)
Archaeological data from the highlands of Eastern Turkey unfortunately does not provide tangible evidence for the transformation of the earliest village communities into the institutional societies of the Urartian State period. The first cities, advanced agricultural activities, mass production and developed commercial activities, however, started to appear after the establishment of the Urartian State, as a result of central authority and institutionalization. There is a sharp difference between the pre-Urartian and Urartian State periods, which makes it difficult to understand the stages of the state transformation process. This article discusses political and social changes and stages of state formation through the archaeological data, chronologically. The emergence of the first elites in the Eastern Anatolian plateaus goes back to the Middle Bronze Age with the appearance of the kurgan burials, which is mostly observed in Northeastern Anatolia. After a while, another organizational process started in the Van Lake Basin during the Late Bronze-Early Iron Age, which is characterized by the construction of fortresses and cemeteries including bronze and iron weapons. This means the state formation in the region and the establishment of the Urartian State rises from the organizational process of the semi-nomadic tribes dealing with animal husbandry during the Early Iron Age, rather than farmer societies engaged in agriculture. In other words, the state formation in the Eastern Anatolian highlands did not develop from the agricultural model of “village, city and state”. Rather, it is observed in the form of “village, state and city”